Design and implementation of a novel three‐phase cascaded half‐bridge inverter. Issue 8 (1st June 2016) - Hasan, Md Mubashwar; Abu‐Siada, A.; Islam, Md. Rabiul
Abstract : In this study, a new circuit topology of a three‐phase half‐bridge multilevel inverter (MLI) is proposed. The proposed MLI that consists of a cascaded half‐bridge structure along with a modified full‐bridge structure requires less number of dc‐power supplies and power semiconductor devices, e.g. insulated gate bipolar transistors and diodes when compared with the existing MLI topologies, which significantly reduces the size and cost of the inverter. Two different structures: isolated and non‐isolated dc‐power supply‐based three‐phase half‐bridge MLIs are investigated. A number of generalised methods are proposed to determine the magnitude of the input dc‐power supplies that has a great impact on the number of levels of the output voltage waveform. To verify the feasibility of the proposed MLI topology, a scaled down laboratory prototype three‐phase half‐bridge MLI is developed and the experimental results are analysed and compared with the simulation results. Experimental and simulation results reveal the feasibility and excellent features of the proposed inverter system.